The Influence Of School Principals' Leadership On The Development Of Teachers' Social Competencies At High School State 4 Jambi City - Nopriansyah, Ahmad; Zul Bahri, Zul; Rahman, KA (FKIP Universitas Jambi, 2024)
This research aims to explore the influence of principal leadership on the development of teachers' social competence in 4 state junior high schools in Jambi City. Teachers' social competence is a crucial factor that plays a role in increasing the effectiveness of teaching and interactions with students. Through an empirical study approach, this research analyzes how the principal's leadership style can influence and develop teachers' social abilities, including communication, cooperation and interpersonal relationships in the school environment.